Microstructural Development and Mechanical Properties for Reactive Air Brazing of ZTA to Ni Alloys Using AgCuO Braze Alloys. Issue 12 (30th May 2014) - Prevost, Erica; DeMarco, A. Joseph; MacMichael, Beth; Joshi, Vineet V.; Meier, Alan; Hoffman, John W.; Walker, William J.; Kuhn, Bernd; Beck, Tilmann
<x xml:space="preserve">Abstract</x> In the current study, nickel (Ni) alloys were heat treated to form an oxide layer prior to reactive air brazing (RAB) joining to zirconia‐toughened alumina (ZTA). In the current study five Ni alloys were evaluated. The ZTA studied had compositions of 0–15 wt% zirconia and 0–14 wt% glass. Four point‐bend tests were performed to evaluate the joint strength of ZTA/ZTA and ZTA/nickel alloys brazed with Ag 2 wt% CuO braze alloys. The joint strength is not a function of the ZTA composition, but the strength is a strong function of the chemistry and microstructure of the oxide layer formed on the nickel alloy. An increase in the aluminum content of the Ni alloy resulted in an increase of the thickness of alumina in the oxide layer and was directly proportional to the bond strength.